Electrical properties anisotype heterojunctions n-TiO2:Mn/p-CdTe - Mostovyi, A. I.; Brus, V. V.; Maryanchuk, P. D.; Ulyanitskii, K. S. (Technology and design in electronic equipment, 2013)
The authors have investigated electronic properties of n-TiO2:Mn/p-CdTe anisotype heterojunctions, produced by the method of electron-beam evaporation of TiO2:Mn film on single-crystal CdTe substrates in vacuum. The dominant mechanism of charge transport in the forward and reverse bias has been established.